2017
DOI: 10.1186/s12872-017-0571-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chronotropic response to physical activities in heart failure patients

Abstract: BackgroundWhile exercise-based cardiac rehabilitation has a beneficial effect on heart failure hospitalization and mortality, it is limited by the presence of chronotropic incompetence (CI) in some patients. This study explored the feasibility of using wearable devices to assess impaired chronotropic response in heart failure patients.MethodsForty patients with heart failure (left ventricular ejection fraction, LVEF: 44.6 ± 5.8; age: 54.4 ± 11.7) received ECG Holter and accelerometer to monitor heart rate (HR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The present findings add to a growing body of evidence suggesting that lower levels of PA may independently associate with poor transplant clinical outcomes, independent of other psychosocial characteristics. Our findings extend previous work in pulmonary and cardiac samples demonstrating that lower levels of actigraphy‐assessed PA are predictive of poorer clinical outcomes. Our work also extends previous findings among lung transplant recipients by demonstrating that greater post‐transplant depressive symptoms also are associated with worse clinical outcomes, independent of PA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings add to a growing body of evidence suggesting that lower levels of PA may independently associate with poor transplant clinical outcomes, independent of other psychosocial characteristics. Our findings extend previous work in pulmonary and cardiac samples demonstrating that lower levels of actigraphy‐assessed PA are predictive of poorer clinical outcomes. Our work also extends previous findings among lung transplant recipients by demonstrating that greater post‐transplant depressive symptoms also are associated with worse clinical outcomes, independent of PA.…”
Section: Discussionsupporting
confidence: 86%
“…Recent case series data suggest that cardiothoracic transplant recipients exhibit lower levels of PA within 1 year of transplantation compared with age‐ and gender‐matched controls and that PA may be improved through intervention . In addition, lower levels of PA have been associated with poorer clinical outcomes in both pulmonary and cardiac patients. Although few studies have examined PA and related factors following transplant, we recently demonstrated that lower functional capacity (eg, six‐minute walk distance [6MWD]) was independently associated with worse clinical outcomes after lung transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic dysfunction (AD) plays a major role in both sudden cardiac death and syncopes as well as in HF . In addition, HF is also associated with chronotropic incompetence (CI) . CI leads to the limitation of physical activity and amplifies the HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that adverse events (such as decreased SPO 2 , tachycardia and frailty) frequently occur in elderly patients. Referencing exercise physiology, we believed APMHR and VO 2max were novel but valuable to cardiac rehabilitation, primarily with accurate evaluation to physiological responses [26,27]. Shen et al reported that patients whose heart function decreased more than 50% could not tolerate 70% of APMHR exercises [26].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid harm from unaccustomed vigorous exercise, the studies of aerobic and resistance exercise were payed more attention to maximal oxygen consumption (VO 2max ) [14]. Guaranteeing the safety, the proper exercise intensity would be assessed by accurate prediction of age-predicted maximal heart rates (APMHR) and VO 2max [15]. However, exercise-based cardiac rehabilitation has not been recommended for patients after surgery, the adoption of the guidelines is negatively impacted by insufficient recognition of APMHR.…”
Section: Introductionmentioning
confidence: 99%